2020
DOI: 10.1016/j.isci.2020.101026
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cGAS-Mediated Interferon Response Facilitates Transgene Expression

Abstract: DNA transfection is often the bottleneck of research and gene therapy practices. To explore the mechanism regulating transgene expression, we investigated the role of the cGAS-STING signaling pathway, which induces type-I interferons in response to DNA. We confirmed that deletion of cGAS enhances transgene expression at the protein level by~2-to 3-fold. This enhancement is inversely correlated with the expression of interferons and interferon stimulated genes (ISGs), which suppress expression of transfected ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…We then examined the mRNA expression level of a number of known downstream target genes of the cGAS-STING pathway. Consistent with the previous studies ( Sun et al, 2013 ; Parkes et al, 2017 ; Fu et al, 2020 ), Talazoparib treatment greatly upregulated the expression of type I interferons (IFN; Inf-α and Inf-β ), pro-inflammatory cytokines ( Ccl5 and Cxcl10 ), and interferon-stimulated genes (ISGs; Isg15 , Mx1 , Mx2 , and Ifit3 ) ( Figure 1F , Figure 1—figure supplement 1A ). To examine whether the cGAS-STING pathway is necessary for the PARPi-induced innate immune signaling, we depleted cGAS using two independent short hairpin RNAs (shRNAs) ( Figure 1G ).…”
Section: Resultssupporting
confidence: 90%
“…We then examined the mRNA expression level of a number of known downstream target genes of the cGAS-STING pathway. Consistent with the previous studies ( Sun et al, 2013 ; Parkes et al, 2017 ; Fu et al, 2020 ), Talazoparib treatment greatly upregulated the expression of type I interferons (IFN; Inf-α and Inf-β ), pro-inflammatory cytokines ( Ccl5 and Cxcl10 ), and interferon-stimulated genes (ISGs; Isg15 , Mx1 , Mx2 , and Ifit3 ) ( Figure 1F , Figure 1—figure supplement 1A ). To examine whether the cGAS-STING pathway is necessary for the PARPi-induced innate immune signaling, we depleted cGAS using two independent short hairpin RNAs (shRNAs) ( Figure 1G ).…”
Section: Resultssupporting
confidence: 90%
“…37 In regards to nonviral gene delivery, the inhibition of STING with small molecule inhibitors (C176, C178) has been shown to enhance transgene expression by up to 3-fold in a variety of cell lines, including primary T cells. 38 These previous studies and our observations collectively emphasize the importance of the STING DNA sensing pathway and suggest that targeting STING for inhibition may be an effective strategy to improve the potency of gene therapy treatments.…”
Section: Differences In Dna Sensing Pathwayssupporting
confidence: 71%
“…In addition, our research group found that inhibition of cGAS by gene knockout or chemical inhibition can increase transgene expression at the transcriptional level, and that this increase is negatively correlated with IFN and interferon-stimulated gene (ISG) expression (78). Thus, targeting the cGAS-STING signaling pathway is likely an effective strategy for gene therapy and nucleic acid drug development.…”
Section: A Variety Of Nucleic Acid Species Are Sensed By Cgas Cgas Re...mentioning
confidence: 99%